GITRL-armed Delta-24-RGD oncolytic adenovirus prolongs survival and induces anti-glioma immune memory. Issue 1 (5th June 2019) - Rivera-Molina, Yisel; Jiang, Hong; Fueyo, Juan; Nguyen, Teresa; Shin, Dong Ho; Youssef, Gilbert; Fan, Xuejun; Gumin, Joy; Alonso, Marta M; Phadnis, Sheetal; Lang, Frederick F; Gomez-Manzano, Candelaria
Abstract: Background: Viroimmunotherapy is evolving as a strong alternative for the standard treatment of malignant gliomas. Promising results from a recent clinical trial testing the anticancer effect of Delta-24-RGD in patients with glioblastoma suggested the induction of antitumoral immunity after viral administration. To further enhance the anti-glioma immune effect, we have armed Delta-24-RGD with the costimulatory ligand GITRL (Delta-24-GREAT [Glucocorticoid Receptor Enhanced Activity of T cells]). Methods: We tested the infectivity and replication of Delta-24-GREAT, and the expression of ectopic GITRL in human and murine glioma cell lines. In vivo experiments involved the intracranial implantation of glioma cells into an immunocompetent model to study the anticancer effect, and rechallenging experiments to study long-term protection. Phenotypic and functional characterization of lymphocyte populations were performed by FACS and ELISA for Th1 cytokines expression, respectively. Results: Our results showed that Delta-24-GREAT infects and induces the expression of GITRL. Delta-24-GREAT prolonged the survival of glioma-bearing immunocompetent mice and resulted in both anti-viral and anti-glioma immune responses, including increased frequency of central memory CD8 + T cells. Rechallenging the surviving mice with a second implantation of glioma cells did not lead to tumor growth; however, the surviving mice developed lethal tumors when B16/F10 melanoma cells were implanted intracranially, strongly indicating that the immune response was specific for glioma antigens. Conclusions: GITRL-armed Delta-24-RGD treatment results in an antigen-restricted antitumor memory, an enhanced anti-glioma effect, and the generation of central immune memory. Our results strongly indicate that this strategy represents a vertical advance in virotherapy designed to treat patients with malignant brain tumors.